Fibrinolytic bacteria of Indonesian fermented soybean: preliminary study on enzyme activity and protein profile - SYAHBANU,Fathma (2020)
Abstract A number of fibrinolytic enzyme producing microorganisms have been identified in various fermented food in Asia, such as from Red Oncom, Tempe, Terasi (Indonesia), Natto (Japan), Douchi, Soy paste (China), Meju, Kimchi, Jeot-gal, Tofuyo, Chungkook-jang, Soybean paste and Doen-jang (Korea). The high protein content in soybean is potential to promote the growth of proteolytic and fibrinolytic producing microbes. This study investigated several fibrinolytic bacteria, isolated from the moromi stage of the fermented soysauce production. The fibrinolytic activities of the isolates were confirmed in a fibrin plate assay, and all 3 potential isolates (K1, K2, and K3) were identified as Gram positive, rod shaped, and spore forming bacteria. Moreover, analysis of the sequences encoding 16S rRNA gene, revealed K1 as Bacillus cereus, K2 as Bacillus subtilis, and K3 as Bacillus cereus. SDS PAGE analysis demonstrated different protein profile of the cell free supernatant of isolates grown in LB media during fermentation, which ranged from 18.40-45 kDa.